2019
DOI: 10.15561/18189172.2019.0405
|View full text |Cite
|
Sign up to set email alerts
|

Features of physical development and somatotype of girls and women involved in fitness

Abstract: Purpose : Comparative analysis of the physical development features and somatotype of girls and women involved in fitness. Material : The experiment involved 95 girls and women, divided into 2 groups. Group 1 - 48 girls (36.04 ± 0.19) years, Group 2 - 47 women (43.26 ± 0.22) years, (p <0.01). Participants practiced fitness 2-3 times a week. The duration of the training was 60 minutes. It was determined the body mass and body length, wrist circumference, waist and hips circumferences. The TANITA BC 587 analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The rational sequence of performing physical exercises in daily, weekly and monthly cycles ensures the transition of the body's physical reactions into long-term adaptation to physical activity (Lee & Shiroma, 2014). A positive effect from the realization of physical activity is achieved only when motor activity is combined with the action of the next motorcycle, through the compensation of energy resources (Hamaguchi et al, 2020;Podrigalo et al, 2019). This means that the basis for the implementation of effective physical activity is the systematic effect of the load and the regularity of its repetition (Exel et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…The rational sequence of performing physical exercises in daily, weekly and monthly cycles ensures the transition of the body's physical reactions into long-term adaptation to physical activity (Lee & Shiroma, 2014). A positive effect from the realization of physical activity is achieved only when motor activity is combined with the action of the next motorcycle, through the compensation of energy resources (Hamaguchi et al, 2020;Podrigalo et al, 2019). This means that the basis for the implementation of effective physical activity is the systematic effect of the load and the regularity of its repetition (Exel et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%
“…Our data are consistent with the reported data (Peterman et al, 2019) that showed the importance of the indicators of the functional state of the cardiorespiratory system, coordination abilities, and physical fitness. The relationships between indicators of physical development, functional status, and coordination abilities have been confirmed (Güler & Yüksek & Göksu, 2020;Podrigalo, et al, 2019). We used the data of factor analysis to select the most informative criteria for the effectiveness of the proposed health-enhancing exercise program.…”
Section: Discussionmentioning
confidence: 93%